Algerian Prickly Pear Seed By-Products: Fatty Acids Composition, Antioxidant, Enzyme Inhibitory Activities towards Tyrosinase, Urease, α-Amylase, and Cholinesterase, along with the Ability to Protect from Thermal Protein Denaturation - Nassiba Chafaa; Camelia Mosbah; Latifa Khattabi; Karima Malaoui; Wafa Zahnit; Mohamed El Amine Smaali; Faiza Houri; Yazid Medfouni; Khalid Mashay Al-Anazi; Ahmad Ali (MDPI AG, 2024)
Prickly pear seed is a source of the most expensive oil in the world, which is rich in vitamins and polyunsaturated fatty acids. Its extraction generates a large quantity of press cake. These two by-products need to be valued. The current study aimed to assess the fatty acid composition of oil and the phytochemical composition of press cake. In addition, the antioxidant and the inhibition of thermal protein denaturation effects of both Algerian seed by-products were evaluated with their inhibitory action against the activities of urease, tyrosinase, α-amylase, and cholinesterase enzymes. The GC MS analysis result revealed the richness of our oil in linoleic (74%) and palmitic (13%) acids methyl esters, respectively. The chemical composition of press cake was characterized by a high value of dry matter (94.94 ± 0.05%), especially the carbohydrates (85.13 ± 0.94%). The results of antioxidant activity presented by IC50 and A0.5 ranged from 7.51 ± 0.03 to 88.10 ± 0.92 µg/mL. Furthermore, the IC50 values were 40.19 ± 1.21 and 61.18 ± 0.03 µg/mL in thermal protein denaturation assay, and ranging from 22.97 ± 0.72 to 385.99 ± 0.27 µg/mL for the inhibition of enzymatic activities. These results indicate that the studied oil can be one of the strongest oils for its impressive effects and also encourage us to reuse its press cake in feed livestock.